Exploring The Evolution Of Sport Science History Research In The World: A Bibliometric Perspective (1980–2025) - Jalal kanan, fahmi dababsi; Igor Georgievich , Maksimenko; Alatrash, Mahmoud (Journal of Sport Science Technology and Physical Activities, 2025)
History Sports Science grew as an interdisciplinary field of research in cultural, physiological, and historical aspects of the concept of sport as time progressed. The present study examines worldwide trends in the 4d) academic evolution of sport science history using a bibliometric methodology without pretending to be an exclusive novelty. Descriptive statistics of annual publications, citation counts, top cited works, and publication languages were discussed in detail and presented in the main text. These results reflect the development of the field, the impact of key papers and the internationalization of science. Finally, co-citation, bibliographic coupling and keyword co-occurrence analyses have also been used to detect intellectual connections, thematic structures and collaboration networks among authors. We retrieved data only from the Web of Science to guarantee accuracy, and the VOSviewer was used for bibliometric mapping and visualization. The results reveal the centers of journals, topics and influential researchers in sport science history. Instead of leaving much to the imagination elsewhere, the article has left something substantive on which other scholars, educators, and policy makers may stand with (partly) shared confidence, engaged in continuing to take learning and work in this domain further.